E7080, a multi-targeted tyrosine kinase inhibitor suppresses tumor cell migration and invasion - Macleod Kenneth; Patel Hitesh; Mason Susan; Glen Hilary; Brunton Valerie G (BMC Cancer, 2011)
Abstract Background E7080 is an orally active multi-targeted kinase inhibitor whose targets include vascular endothelial growth factor receptors (VEGFR), fibroblast growth factor receptor (FGFR) and platelet derived growth factor receptors (PDGFR). It has been shown to inhibit tumor angiogenesis by targeting endothelial cells. A number of the targets of E7080 are also expressed on tumor cells and here we have looked at the direct effects of E7080 on tumor cell behavior. Methods Using a panel of human tumor cell lines we determined the effect of E7080 on cell proliferation, migration and invasion. Inhibition of FGFR and PDGFR signaling in the cells was measured. Results E7080 had little effect on tumor cell proliferation. However, it blocked migration and invasion at concentrations that inhibited FGFR and PDGFR signaling. Knock-down of PDGFR-β in U2OS osteosarcoma cells also inhibited cell migration which, could not be further inhibited in the presence of E7080. Furthermore, E7080 could not inhibit the migration of a PDGFR negative cell line. Conclusion E7080 does not significantly affect tumor cell proliferation but can inhibit their migration and invasion at concentrations that both inhibit its known targets and are achievable clinically.